Does Halal Product Availability and Accessibility Enhanced Halal Awareness and Intention to Purchase Halal Packaged Food Products: Malaysia and Thailand’s Halal Industry perspective - Hasnizam Shaari; Norzieiriani Ahmad; Salniza Md. Salleh; Sany Sanuri Mohd Mokhtar; Rushami Zien Yusoff; Anon Khamwon; Nitipon Putatchote (International Journal of Supply Chain Management, 2020)
Halal industry is a huge business. The business is not Muslim-specific yet some of the non-Muslim consumers become a regular user of halal products due to holistic conception of halal itself-cleanliness and wholesomeness. Such development shows that halal awareness is evident among Muslim and non-Muslim consumers. Halal awareness has been cited as the major determinant for intention to purchase halal products but lack is understand what made up halal awareness that lead to halal consumption. Rooted from ATAR model, this study aims to examine the effect of halal product accessibility and availability on halal awareness of packaged food products in Malaysia and Thailand consumers. In addition, halal awareness also proposed to influence intention to purchase halal packaged food products. The study among 760 consumers in Malaysia and Thailand revealed that accessibility enhanced halal awareness for Muslim-dominant country whereby availability plays a crucial role in explaining halal awareness for non-Muslim-dominant country. Theoretical and managerial implication as well as future direction of the study is discussed at the end of the article.